More compact orthogonal drawings by allowing additional bends - Jünger, Michael; Mutzel, Petra; Spisla, Christiane (Technische Universität Dortmund, 2018)
Compacting orthogonal drawings is a challenging task. Usually, algorithms try to compute drawings with small area or total edge length while preserving the underlying orthogonal shape. We suggest a moderate relaxation of the orthogonal compaction problem, namely the one-dimensional monotone flexible edge compaction problem with fixed vertex star geometry. We further show that this problem can be solved in polynomial time using a network flow model. An experimental evaluation shows that by allowing additional bends could reduce the total edge length and the drawing area.
Information;Jg. 9, Heft 7. S. 153-1-153-24
Keywords: Orthogonal compaction; Graph drawing; Total edge length; Bends; Flow-based compaction; 004; Graphenzeichnen